Art and physical activity as protective factors of medicine students' mental health (Research, Society and Development, 2022)
Introduction: The mental health care of university students in the health area has been the subject of numerous discussions. The practice of physical activities on a regular basis generates many benefits to the human body, being relevant the questioning about its protective power in the psychic sphere. In relation to artistic activity, it presents itself in several possibilities and is popular in the field of medicine as a form of treatment, known as “therapy with art”. Objective: To analyze the protective effects of physical activity and artistic activity on the mental health of medical students at Tiradentes University, in addition to comparing their results and understanding the possible mechanisms. Methodology: This is a cross-sectional, exploratory, descriptive and quantitative study. Data were collected through self-administered questionnaires using the Google form, containing the sociodemographic questionnaire and the Self-Reporting Questionnaire (SRQ-20), after signing the Free and Informed Consent Form (ICF). Results: About 53.7% of the entire group showed signs of suffering from the SRQ-20. The percentage of respondents who practice physical activities who showed no signs of psychological distress was 52.3%, while only 33% of non-practitioners obtained the same result. Regarding the artistic activity, 55.9% of practitioners showed no signs of mental suffering, while 43.4% of non-practitioners had no psychic injury. Conclusion: Although physical activity has a more significant power to protect mental health, artistic activity, to a lesser extent, should also be considered a protective instrument for the psychic health of the group in question.